The ABC Model: Commentary from the Perspective of the Two Pyramids Model of Radicalization - McCauley, Clark (Terrorism and political violence, 2022)
In this commentary, I compare the ABC model of radicalization with the Two Pyramids model of radicalization. Both models distinguish radicalization of opinion from radicalization of action. Beyond this agreement are questions about the concepts deployed in advancing the ABC model and research issues relating to applications of the two models. I conclude with an optimistic assessment of recent progress in research on terrorism, including the suggestion that deradicalization of action may be forwarded by giving up on deradicalization of opinion.